(3MGTjI TQM GddeYI GdOeTbjIs - (3GdGHGOFj, GdaGQSj, eMeO LYaQ Hf eMeO Uaj, cGf MjG bHd (B1313 (3g`s ((3GdeDdas)
(3ChdgG (B:s
... (3haj ZGjI GdeQGe CWHb GdCUMGH aj cJH GdaJGhi Ydi Gf GdaQV hGdfad CMO hNeShf aj Gdjhe hGddjdI hdge Ydjg QhGjGJ cKjQI hhQOJ Hg QhGjI CNQi JJVef GdfbjVI Yf Pdc (B...s
(3BNQgG (B:s
... (3hIEP bO YQaJ Gf gPg GdCNHGQ GdeSJajVI GdeYJHQI ZGjI GdGYJHGQ JOd Ydi GdeWdhH ef ZjQ bUhQ hEPG QLYJ GdHUQ cQJjf dG JQi ajgG ef aWhQ(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B3\195s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3abg GdePGgH GdCNQis